Ultrasonic fuel reprocessing in mercury - Tarpley, W. B.; McKinney, C. Dana.; U.S. Atomic Energy Commission.; Aeroprojects Incorporated. (United States Atomic Energy Commission, Technical Information Service, 1961)
The introduction of vibratory motion at an ultrasonic frequency into the corrosive, high temperature, pressurized and radioactive environment, encountered in the reprocesssing of fuel elements in liquid mercury system has led to significant improvement in dissolution rates.
"Aeroprojects Incorporated."
"Contract No. AT(30-1)-1836."
"March 1961."
"NYO-9578 ; Chemical Separations Processes for Plutonium and Uranium."
Includes bibliographical references (pages 43-44).
Keywords: Reactor fuel reprocessing. / fast / http://id.worldcat.org/fast/1090525; Mercury. / fast / http://id.worldcat.org/fast/1198509; Mercury. / http://id.loc.gov/authorities/subjects/sh85083794; Reactor fuel reprocessing. / http://id.loc.gov/authorities/subjects/sh85111635